ChemInform Abstract: Recent Advances in the Synthesis of Fluorinated Aminophosphonates and Aminophosphonic Acids. Issue 33 (25th July 2013) - Turcheniuk, Kostiantyn V.; Kukhar, Valery P.; Roeschenthaler, Gerd‐Volker; Acena, Jose Luis; Soloshonok, Vadim A.; Sorochinsky, Alexander E.
Abstract Review: 125 refs.